Healing with plants in the American and Mexican West - Kay, Margarita Artschwager (University of Arizona Press, 1996)
Disenchanted with biomedicine and dismayed by its cost, increasing numbers of people are seeking alternative therapies such as the healing plants discussed in this book. Plant medicine is a billion-dollar business: health food stores, small yerberias, and even giant grocery store chains carry hundreds of medicinal herbs. By one estimate, up to one-third of the U.S. population uses alternative medicine - generally in addition to conventional therapy and commonly without telling their doctors.